A Strategy for Reducing Maternal Mortality in Rural Kenya - Masaba BB; Mmusi-Phetoe R (Dove Medical Press, 2023)
Brian Barasa Masaba, Rose Mmusi-Phetoe Department of Health Studies, University of South Africa (UNISA), College of Human Sciences, School of Social Sciences, Pretoria, South AfricaCorrespondence: Brian Barasa Masaba, Email 63714094@mylife.unisa.ac.zaBackground: Migori County is categorized among regions with worst maternal survival rates in Kenya. The county's current maternal mortality ratio (MMR) is 673 deaths per 100  000 live births. A need exists for a context-specific strategy to mitigate the persistent high maternal mortalities in rural Kenya. The researchers aimed to develop a strategy for reducing the maternal mortality ratio (MMR) in Migori, Kenya.Methods: An explanatory sequential mixed methods design was utilised. The design was characterised by two separate studies, an initial quantitative followed by a qualitative study. The final phase entailed integration of data from the two separate studies. The findings, extensive literature review and three delays of maternal mortality theoretical framework informed the development of the strategy.Results: The strategy for implementation considered three strategic areas, namely, interventions targeting first delays, interventions targeting second delays, interventions targeting third delays.Conclusion: The priority interventions needed are those that enable: 1) Pregnant mothers to receive quality peripartum care in Migori hospitals, 2) Strengthened and efficient referral systems of obstetric emergencies and 3) Community knowledge empowerment on safe pregnancy and culture shift. These interventions would significantly transform the health-care system towards maternal mortality reduction. The Kenyan government and non-profit organisations should be involved in the implementation of the proposed strategy.Keywords: community empowerment, determinants, health systems, interventions, maternal delays, maternal mortality, obstetric care, obstetric complications, pregnancy, quality care, referral, strategy